THE STUDENTS' MENTAL PROCESS OF CRITICAL THINKING SKILL ANALYZING LITERARY WORK - Moh. Hafidz; Pratiwi Retnaningdyah; Ali Mustofa; Slamet Setiawan; Oikurema Purwati (STKIP PGRI Jombang, 2022)
Purposive behavior directly convey the students' mental process of critical thinking skill in analyzing literary work and producing composition. There is a theoretical and practical gap between the critical thinking process and products. This research descriptively designs to answer research problems. The previous study investigates the students’ written products and claims that they have a good critical thinking when they have multi references. In contrast, critical thinking is process of mental which students not only finding new information from some resources but also realizing their learning objective, identifying problems to motivate themselves to write a composition. As the results, the students who have a low level of critical thinking skill and they strongly aware of their gaps will analyze the literary work well, and a high level of critical thinking makes a power of analysis, an accurate and precise composition. Student’s mental process of critical thinking appears on the students’ process to read and cite a number of literacies, detect self-problem, encourage themselves to make a written texts based on the learning outcomes.